Bacterial Etiology and Antibiogram of Lower Respiratory Tract Infections at a Tertiary Care Hospital in Kathmandu, Nepal - Chalise, Bimal Sharma; Regmi, Ramesh Sharma; Basaula, Yuba Nidhi; Neupane, Jenish; Ghimire, Sandesh; Adhikari, Sanjib; Rijal, Komal Raj (Journal of National Heart and Lung Society Nepal, 2024)
Background: Globally common, lower respiratory tract infections (LRTIs) are especially difficult to manage in developing countries, where identifying the specific cause and determining the correct antibiotic treatment are major challenges. Methods: A cross-sectional study was conducted on patients with lower respiratory tract infections (LRTIs). A total of 1912 sputum samples were investigated for bacterial growth using standard microbiological methods. Isolates were identified through cultural, microscopic, and biochemical analyses, and subsequently subjected to antibiotic susceptibility testing. Results: Overall bacterial prevalence in sputum was found to be 11.7%. K. pnuemoniae was the predominant isolate recovered from 4.6% specimens. Altogether, isolates from 11 different genera were recovered in the study. Bacterial prevalence was more among male (13.8%) and people from age group 76-90 (16.7%). Similarly, bacterial LRTIs were found more prevalent during spring (14.4%) and summer (12.7%) seasons. All these associations were found statistically significant (p-value<0.01). AST pattern revealed most of the first and second-line drugs were ineffective against isolated organisms. For GNB, amikacin among first and second-line was found to be the most effective drug, whereas for S. aureus, ceftazidime and cefepime (100%) were found to be effective drug. Conclusion: Detection of bacterial agents from sputum and understanding the resistance pattern can be a basis for successful antimicrobial therapy and mapping a way-forward to mitigate the issue of MDR in Nepal.